The Sustainable Development of the Tourism Industry and Social Acceptance - Surmanidze, Megi; Beridze, Rostom (European Journal of Sustainable Development, 2025)
As the tourism industry expands in scale, the importance of sustainable development is also increasing (World Tourism Organization [WTO], 2023). The principles of sustainable development aim to guide industry activities in a beneficial direction, ensuring the greatest possible advantages for society, nature, and the environment. Tourists, in addition to being consumers, are also important stakeholders in the industry, as highlighted in the principles of sustainable development. The economic and social development of the sector, including practices in the Adjara region, significantly depends on their choices and level of satisfaction. However, evaluations of organizations providing tourism services often reveal negative feedback from tourists. Complaints frequently relate to rude, indifferent, or inattentive attitudes. According to social acceptance theory, such issues arise when relationships between different parties are shaped by aggression and rejection rather than cooperation. Since tourists act both as stakeholders and consumers, it is essential that they have the right and opportunity to receive hospitality services in a healthy social environment. Representatives of the tourism industry also bear ethical and social responsibilities toward them. This article discusses the principles of sustainable tourism development and the concept of social acceptance. In particular, it examines the attitudes of tourism organizations in Adjara toward tourists. The main aim of the study was to determine the role of social acceptance in ensuring the sustainable development of the industry. The study was conducted through an online questionnaire. The results revealed that social acceptance plays an important role in the economic development of the industry. It also demonstrated the significance of sustainable development principles, particularly visitor satisfaction. Keywords: Tourism Industry, Sustainable Development, Social Acceptance